1990
DOI: 10.1073/pnas.87.20.7829
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin switch circular DNA in the mouse infected with Nippostrongylus brasiliensis: evidence for successive class switching from mu to epsilon via gamma 1.

Abstract: We have characterized immunoglobulin switch circular DNA in mice infected with the nematode parasite Nippostrongylus brasiiensis. Two kinds of circular DNA were identified in the lymph nodes as excision products of switch recombination of immunoglobulin heavy-chain constant region (CH) genes. One is a recombinant between C., and C,1 (yl circle), and the other is a recombinant between Cy1 and C, (E circle). In the E circle, a short piece of switch ,u (S,,) sequence was inserted between SE, and Sy7 sequences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
60
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 31 publications
10
60
0
2
Order By: Relevance
“…These results suggest that IL-21 increases IgG1 production by the mechanism that is independent from the induction of germ line C␥1 transcription. Regarding the point, Yoshida et al 40 have shown that switch recombination to IgE occurs at least in part in a successive manner: first from IgM to IgG1, and then from IgG1 to IgE. Therefore, it is possible that IL-21 increases IgG1-producing cells through the inhibition of switching from IgG1 to IgE.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that IL-21 increases IgG1 production by the mechanism that is independent from the induction of germ line C␥1 transcription. Regarding the point, Yoshida et al 40 have shown that switch recombination to IgE occurs at least in part in a successive manner: first from IgM to IgG1, and then from IgG1 to IgE. Therefore, it is possible that IL-21 increases IgG1-producing cells through the inhibition of switching from IgG1 to IgE.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analyses of Ig isotype switching support a model of alignment of two switch region sequences which are 5 Ј to each heavy chain region followed by looping out and deletion of the intervening DNA (3). Such excised switch circular DNA has been directly demonstrated in murine (4)(5)(6)(7)(8) and human B cells (9,10). Definitive proof of the ability of a signal to function as an isotype switch factor requires demonstration of it's ability to induce the appropriate deleted switch circular DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation and existence of IgE memory B cells is controversial and poorly understood (50)(51)(52)(53)(54)(55)(56). It has been suggested that a significant fraction of IgE memory resides in the IgG1 compartment, with generation of a memory IgE response resulting from sequential switching of IgG1 memory B cells to the IgE B cell lineage (50,54,(57)(58)(59)(60)(61)(62)(63)(64). While our studies have not directly addressed this issue, it is interesting that we and others have observed that both primary and memory IgE responses occur prior to IgG1 responses in our immunization and asthma models, perhaps indicating that the vast majority of IgE responses do not develop by a sequential switching mechanism through an IgG1 B cell intermediate.…”
Section: Figurementioning
confidence: 99%